Parenting Practices in Guyana and Trinidad and Tobago: Connections to Preschoolers Social and Cognitive Skills - Roopnarine, Jaipaul L; Wang, Yan; Krishnakumar, Ambika; Davidson, Kimberly L (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2014)
Abstract This report presents the findings of two studies that examined the degrees of parental warmth and control and their associations with children’s social and intellectual skills in two groups of Caribbean families. In Study 1, 139 Indo Guyanese mothers reported on their use of maternal warmth and control and in Study 2, 180 mothers and 180 fathers from diverse ethnic groups in Trinidad reported on their use of warmth and control in parenting their preschool-aged children. In both studies, preschool teachers provided assessments of children’s prosocial behaviors, anger, and their divergent and convergent cognitive skills. Analyses revealed two clusters of Guyanese mothers: one group was higher in warmth and lower in control and the other was lower in warmth and higher in control. Identical clusters were found for Trinidadian mothers and fathers. Trinidadian mothers and fathers reported using similar levels of warmth with preschoolers. Only among Guyanese families did children fare differently in social and intellectual skills between the two clusters of parents. Data are interpreted in terms of variability in the use of both warmth and behavioral control as prevailing practices in Caribbean cultural communities and their implications for childhood developmental outcomes.